Asymmetric Enzymatic Hydration of Unactivated, Aliphatic Alkenes. Issue 1 (30th November 2018) - Demming, Rebecca M.; Hammer, Stephan C.; Nestl, Bettina M.; Gergel, Sebastian; Fademrecht, Silvia; Pleiss, Jürgen; Hauer, Bernhard
Abstract: The direct enantioselective addition of water to unactivated alkenes could simplify the synthesis of chiral alcohols and solve a long‐standing challenge in catalysis. Here we report that an engineered fatty acid hydratase can catalyze the asymmetric hydration of various terminal and internal alkenes. In the presence of a carboxylic acid decoy molecule for activation of the oleate hydratase from E. meningoseptica, asymmetric hydration of unactivated alkenes was achieved with up to 93 % conversion, excellent selectivity (>99 % ee, >95 % regioselectivity), and on a preparative scale. Abstract : Engineered for success : Asymmetric hydration of unactivated, aliphatic alkenes was achieved with a fatty acid hydratase generating chiral alcohols with high conversion, excellent regio‐ and enantioselectivity, and on a preparative scale. Key for high activity is a carboxylic acid decoy molecule that activates the wildtype and engineered enzymes for alkene hydration on alternative substrates.